DETERMINASI DAN INTERVENSI AKAL DALAM MADZHAB USHUL IMAM SYAFI’I - Muhammad Ngizzul Muttaqin; Ahmad Khoiri (TAHKIM, 2020)
One of the main contributors to the development of Islamic law is the intervention of reason in the study of Islamic law. Intervention of reason in the study of Islamic law is a way out if there is a contradiction between the text and reality. One method of ijtihad that combines texts and reason initiated by Imam Shafi'i is qiyas. Qiyas is a method that returns problems to the text of the texts which are assisted by the power and intervention of reason. As a literature-based study and literature study, this study will reveal the intervention of reason in the ushul Imam Syafi'i school of thought, namely the qiyas method.